Software engineering education in medical informatics - Leven, F J (Methods of information in medicine, 1989)
Requirements and approaches of Software Engineering education in the field of Medical Informatics are described with respect to the impact of (1) experiences characterizing the "software misery", (2) status and tendencies in software methodology, and (3) educational status and needs in computer science education influenced by the controversy "theoretical versus practical education". Special attention is directed toward the growing importance of analysis, design methods, and techniques in the professional spectrum of Medical Informatics, the relevance of general principles of systems engineering in health care, the potential of non-procedural programming paradigms, and the intersection of Artificial Intelligence and education. Realizations of and experiences with programs in the field of Software Engineering are reported with respect to special requirements in Medical Informatics.